2017
DOI: 10.1111/bph.13783
|View full text |Cite
|
Sign up to set email alerts
|

CGRP receptor activity in mice with global expression of human receptor activity modifying protein 1

Abstract: BACKGROUND AND PURPOSECGRP is a potent vasodilator and nociceptive neuropeptide linked to migraine. CGRP receptors are heterodimers of receptor activity modifying protein 1 (RAMP1) and either calcitonin receptor-like receptor (CLR; forms canonical CGRP receptor) or calcitonin receptor (CT receptor; forms AMY 1 receptor). The goal of this study was to test whether transgenic mice globally expressing human RAMP1 have increased CGRP receptor activity and whether the receptors are sensitive to human selective anta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…Interestingly, the expression pattern of AMY1 receptor is suggestive of co-localization with CGRP, as discussed below, although this remains to be demonstrated. AMY1 receptors are also present in vascular smooth muscle based on immunostaining (Walker et al 2015) and suggested by functional data from cell culture studies (Bohn et al 2017). CGRP receptor expression in the trigeminal ganglion is possibly involved in signaling mechanisms that may be important for sensitizing mechanisms in facial pain and headache generation.…”
Section: Neuropeptide Receptors In the Trigeminal Ganglionmentioning
confidence: 97%
“…Interestingly, the expression pattern of AMY1 receptor is suggestive of co-localization with CGRP, as discussed below, although this remains to be demonstrated. AMY1 receptors are also present in vascular smooth muscle based on immunostaining (Walker et al 2015) and suggested by functional data from cell culture studies (Bohn et al 2017). CGRP receptor expression in the trigeminal ganglion is possibly involved in signaling mechanisms that may be important for sensitizing mechanisms in facial pain and headache generation.…”
Section: Neuropeptide Receptors In the Trigeminal Ganglionmentioning
confidence: 97%
“…This is in agreement with clinical trial data in patients with stable coronary artery disease, whereby no significant drug-related cardiovascular adverse events were reported [ 85 ]. Additionally, when administered to trigeminal ganglion and smooth muscle cell cultures from human RAMP1 overexpressing mice, with increased CGRP, telcagepant significantly inhibited CGRP induced increases in cAMP production [ 86 ]. This effect was not observed in wild-type mice lacking the human RAMP1, further highlighting the limited preclinical utility of telcagepant.…”
Section: Telcagepant (Mk-0974)mentioning
confidence: 99%
“…Global overexpression of hRAMP1 in all tissues was achieved using mice expressing Cre recombinase under the control of the ubiquitous adenovirus EIIa promoter (Bohn et al 2017). Cultures obtained from vascular smooth muscle and trigeminal ganglia from those global mice showed an increased CGRP receptor activity that could be blocked by drugs such as CGRP receptor antagonists telcagepant and CGRP 8-37 (Bohn et al 2017).…”
Section: Overexpression Of Human Ramp1mentioning
confidence: 99%
“…Global overexpression of hRAMP1 in all tissues was achieved using mice expressing Cre recombinase under the control of the ubiquitous adenovirus EIIa promoter (Bohn et al 2017). Cultures obtained from vascular smooth muscle and trigeminal ganglia from those global mice showed an increased CGRP receptor activity that could be blocked by drugs such as CGRP receptor antagonists telcagepant and CGRP 8-37 (Bohn et al 2017). Mice with global hRAMP1 overexpression display increased vasodilation of the carotid and basilar arteries, and cerebral arterioles after CGRP application (Chrissobolis et al 2010), and decreased angiotensin II-induced hypertension (Sabharwal et al 2010).…”
Section: Overexpression Of Human Ramp1mentioning
confidence: 99%